Letter from Kathleen Raine to Sylvia Skelton, December 12, 1986 - http://id.worldcat.org/fast/52672 (1986)
Part of a collection of correspondence to Robin Skelton from British critic and poet Kathleen Raine. In several of the letters Raine discusses the Temenos magazine, of which she was a founder.